The Effect of Brand Image, Product Quality, and Trust on Sanctuary Purchases - Amelia Dwi PRAMUSHINTA; Ahmad HANFAN; Sari WIYANTI (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the influence of brand image, product quality, and brand trust on purchasing decisions for olive tree goyor sarongs in Tegal City at CV Fahaltex. This study involved 100 respondents selected using a purposive sampling technique. The method used in this study to test whether the residual data is normally distributed is statistical analysis. The test was carried out using the Kolmogorov-Smirnov or Shapiro-Wilk test, depending on the number of samples available in the study. The data analysis method used was multiple linear regression. The results showed that brand image had a positive and significant effect on purchasing decisions, indicated by a significance value of 0.044 (<0.05). Product quality also had a significant effect on purchasing decisions, with a significance value of 0.007 (<0.05). In addition, brand trust had a positive and significant effect on purchasing decisions, with a significance value of 0.000 (<0.05). Simultaneously, brand image, product quality, and brand trust jointly influenced purchasing decisions with a significance value of 0.000. These findings suggest that improvements in these three factors can increase consumer interest and purchasing decisions.